Proposal on Electric ARC Furnace Utilization to Achieve Cost Optimization in Slab Steel Plant PT Krakatau Steel - Supriyadi, Beno; Larso, Dwi (The Indonesian Journal of Business Administration, 2013)
Steel Business environment has changed a lot lately, and competition is getting stronger. The global competitive pressure has changed the nature of economy Causing changes in methods of operation in industries. Faced with these situation, the company must be Able to survive and win the competition by performing measurements include all aspects that are future oriented. Krakatau recently imported a lot of semi-finished slab regarding low price for commercial grade steel. In order to win a competition all the effort was done by continuous improvement to reduce production costs. Steel slab plant is part of an integrated stainless steel production facility of Krakatau Â play the biggest role of production cost responsibility. It is by the caused of the major metallurgical task to convert iron ore to steel and non-metallic rawÂ material to slag. Secondly steel making consume huge slab of electrical energy to melt the solid material to liquid steel. Excellent strategy and controlling tights will get very high benefit to earn much profit.The final assigment is focused on formulating a production strategy based on market requirements and production cost. Key point to get succesfull implementation of these depends on the top management strategy comitment, the Efforts of socialization, and the participation of all staff and employee. The feedback pattern always makes the learning more effective strategic and structured and continuous improvement smootly runs.Â Keyword: cost reduction, formulating strategic production, involvement, feedback pattern